2015
DOI: 10.1080/03079457.2015.1050583
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Neospora caninum in house sparrows (Passer domesticus) in Iran

Abstract: Neospora caninum is an intracellular protozoan parasite with a wide range of intermediate bird hosts. There is little information describing the prevalence and genetic characterization of N. caninum in bird hosts worldwide and in Iran. In this study, a total of 217 brain samples of house sparrow (Passer domesticus) were examined for N. caninum presence by nested polymerase chain reaction targeting the Nc-5 gene. N. caninum DNA was detected in 3.68% (8/217) of sparrows. Sequencing of the Nc5 genomic DNA reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…There is little information on presence of N. caninum in birds in Iran and also in other countries (Abdoli et al 2015 ; Barros et al 2018 ). In Iran, N. caninum infection has been reported 2.8% and 3.7% in sparrows ( Passer domesticus ) (Abdoli et al 2015 ; Bahrami et al 2015 ), 17.3% in chickens ( Gallus domesticus ) (Sayari et al 2016 ), 9.8% and 30.4% in Pigeons ( Columba livia ) (Bahrami et al 2016 ), and 9.9% in hooded crows ( Corvus cornix ) (Table 5 ). The high infection in pigeons is probably related to the pigeon’s diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little information on presence of N. caninum in birds in Iran and also in other countries (Abdoli et al 2015 ; Barros et al 2018 ). In Iran, N. caninum infection has been reported 2.8% and 3.7% in sparrows ( Passer domesticus ) (Abdoli et al 2015 ; Bahrami et al 2015 ), 17.3% in chickens ( Gallus domesticus ) (Sayari et al 2016 ), 9.8% and 30.4% in Pigeons ( Columba livia ) (Bahrami et al 2016 ), and 9.9% in hooded crows ( Corvus cornix ) (Table 5 ). The high infection in pigeons is probably related to the pigeon’s diet.…”
Section: Discussionmentioning
confidence: 99%
“…Bartels et al (1999) reported a significant association between the presence and number of poultry with the increase of seroprevalence and abortion storms related to N. caninum in the farms. The occurrence of N. caninum infection in ground-foraging birds can be used to indicate environmental contamination with N. caninum oocysts (Abdoli et al 2015 ). However, more research is needed to reveal the role of birds in the epidemiology of neosporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 200 g – 250 g of different segments of brain and heart were homogenised with a pestle and mortar in liquid nitrogen, and DNA was extracted using a phenol–chloroform extraction method as described in our recent report (Abdoli et al . 2015 ). To prevent DNA cross-contamination, all materials that were used between different tissue samples were decontaminated with sodium hypochlorite solution (2.5%) and rinsed with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Then the products were sequenced in the forward and reverse directions by Sequetech (Mountain View, CA, USA) (Abdoli et al . 2015 ). The sequences were edited with BioEdit sequence alignment editor (Hall 1999 ), aligned with Nc-5 partial sequences from other hosts by ClustalX2.12 (Larkin et al .…”
Section: Methodsmentioning
confidence: 99%
“…For example, antibodies to N. caninum have been detected 61.5% in eland, 58.5% in zebra, 19.2% in gazelle, 33.3% in warthog, 50% in African buffalo, 30% in lion, 20% in cheetah, and 33.3% in spotted hyena by an agglutination test in Kenya [16], and 8.4% in white-tailed deer by ELISA in Northern Mexico [17]. N. caninum DNA has been found 6% in magpie in Spain by PCR [18], and 3.7% in house sparrows in Iran [19]. These results show that these wild animals may be infected or contact with the parasite.…”
Section: Introductionmentioning
confidence: 99%